A Facile Visible‐Light‐Induced Route to Functionalize Polymeric Substrates by Combining Controlled Radical Grafting Polymerization and Thiol−Yne Click Chemistry with Photoredox Catalyst Ir(ppy)3. Issue 14 (26th May 2014) - Chen, Haochuan; Zhao, Changwen; Li, Ruibo; Ma, Yuhong; Liu, Lianying; Yang, Wantai
<x xml:space="preserve">Abstract</x> With tris(2‐phenylpyridine)iridium (Ir(ppy)3) as a photoredox catalyst, visible‐light‐induced surface‐initiated controlled grafting polymerization and thiol‐yne click chemistry are exploited to functionalize a polymer substrate. This technology offers a robust tool to attach a high concentration of desired functional groups onto the surface of polymeric materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>